Efeitos da Fotobiomodulação no processo de cicatrização da lesão por pressão - (:unkn) unknown (Universidade Brasil, 2022)
Currently, the prevention and treatment of Pressure Ulcer (PU) is the focus of multidisciplinary actions in different health care settings. Photobiomodulation is a form of phototherapy proposed in the treatment of PU, as it is able to modulate the quality and speed of the healing process. The objective of this study was to evaluate the quality of life (QoL) of the individual affected by PU, as well as to evaluate the modulation of the PU healing process, through photobiomodulation. This is a qualitative-quantitative clinical study, in which 10 volunteers with PU participated, treated at home. Participants were randomly divided into two groups, according to the therapeutic intervention: Control Group (n=5); treated with calcium and sodium alginate coating and Photobiomodulation Group (n=5); treated with photobiomodulation, where the PUs received punctual irradiation, 4J/point, on alternate days, with a low power laser emitting at 660 nm, with 100 mW of power, for 40 s. All volunteers in this study received treatment for 4 weeks. Participants QoL was analyzed using the WHOQOL-BREF questionnaire, before and after the interventions. The PU healing process was evaluated by the PUSH instrument, on the 1st, 15th and 29th days. The PUs were photographed in a standardized way, on the respective days, to compare the evolution of the repair process. For data analysis, the Shapiro Wilk normality test and the two way ANOVA test of variance were applied, and the means were compared using the Tukey test with a significance of 5%, being considered statistically different when p<0.05. The perception of QoL in the Photobiomodulation Group was regular in the initial phase of treatment, evolving to very good in the final phase, while the volunteers in the Control Group maintained a very good response from the beginning to the end of the treatment. The evaluation using the PUSH instrument showed a gradual temporal improvement in the PU repair process, regardless of the treated group. The comparison of photographic images revealed that there was a reduction in the staging of PUs in both groups. Therefore, we can conclude that photobiomodulation, in the parameters tested in this study, can be a good alternative in relation to QoL and modulation of the PU healing process.
Keywords: Laser de baixa intensidade; Feridas crônicas; Alginato de cálcio e sódio; Atenção domiciliar; Qualidade de vida; Bioengenharia